Factors influencing the intention to purchase Takaful Medical Card - Nurul Nadzirah, Fai Ros (2025)
The global medical trend rate for 2024 is expected to be 10.1 percent, a rise from 9.2 percent in 2023, which was recorded as the highest has been since 2015. The increase in medical care costs which is about 48% percent is driven by behavioural factors insurer reported that the lack of integration between primary, specialty, and facility care is one of the factors boosting medical care costs. Malaysia can be stated as a country that still low in awareness of having insurance protection for future events, as 84% of the group aged between 18 to 34 years old are still not be insured. As the medical sector is rising in cost, the top three insurance products that are currently needed by Malaysians are Medical and Health insurance. Therefore, this study investigates factors that influence the intention to purchase a Takaful Medical Card. This study was conducted using Google Forms and responded by 150 respondents. All data was analyzed using the software Statistical Package for Social Science (SPSS) by correlation and multiple regression analysis. The conceptual framework for this study is built based on the Theory of Planned Behavior (TPB) as underpinning theory by adding three new variables which are awareness, knowledge, and religion to further explain the intention to purchase a Takaful Medical Card. The result of this study shows that there is positive relationship between each variable towards the intention to purchase Takaful Medical Card. The result also shows that each variable significantly contributes to the dependent variable. In conclusion, this study hoped this research would help to develop the Takaful Industry in Malaysia.